Discourse and media: construction of concepts about person with intellectual disability in advertisements - Carla Maria de Schipper; Denise Gabriel Witzel (Universidade Federal de Santa Maria (UFSM), 2015)
This study was designed in order to understand language work respecting  the construction of conceptions about Intellectual Disabilities in the contemporary discourse and their discursive genesis. The basis of the discourse analysis were advertisements published by an institution of special education in the period of 1980 to 2009. To perform this action, the Analysis of Discourse (AD) from French perspective, especially the concepts of interdiscours, memory and heterogeneity, was used as a theoretical basis. Prior to analyzing, presenting some basic concepts of AD and the various conceptions of disability that have arisen throughout history was proven necessary. The Material for analysis is composed of five advertising texts published on a magazine that represents institutions devoted to the care of people with intellectual disabilities and an advertisement to raise funds. The recovery of memory discourse, considering the socio-historical condition of production of discourse, has given visibility to the different places occupied by the person with intellectual disability in the society in each time reported. At the speeches of subject enunciators, attempts to internalize the social roles focused on educational inclusion have been observed, but at the interdiscours, they proved to be voices that exceeded sediment paradigm of medicalization and work as mission.